Controlling Wrinkle Propagation in the Bilayer System with Thickness‐Gradient. Issue 2 (4th December 2017) - Lim, Jongcheon; Choi, Se‐Jin; Kim, Pilnam
Abstract: In this paper, a novel strategy to control the orientation of nanowrinkles by applying a thickness‐gradient to a bilayer‐system is presented. Surface modification by plasma treatment on ultraviolet light‐curable polysiloxane‐based resin applies biaxial compressive strain, resulting in the formation of randomly oriented nanowrinkles over a large‐area. The thickness‐gradient of the resin, given by the meniscus formed between the groove made with patterned polydimethylsiloxane (PDMS) after spin‐coating of the resin, directed wrinkle propagation. Given the propagation orientation, nanowrinkles were well aligned over a large‐area using a simple and accessible method. Abstract : A strategy to align nanowrinkles on a large‐area with simple steps is introduced. With the existence of thickness‐gradient of the polymer substrate, critical strain for wrinkling varies with different thickness of substrate. When the surface is oxidated by the plasma treatment, nanowrinkles propagate with controlled orientation even though biaxial stress is applied in the process.